Sustainability Issues in the Traditional Cashmere Supply Chain: Empirical Evidence from Kashmir, India - Ishrat SI; Grigg N; Bezuidenhout C; Jayamaha N (MDPI (Basel, Switzerland))
Considering the emerging global markets for the consumption of cashmere products, current sustainability issues prevailing in the traditional cashmere industry are explored in this study. To get a deeper understanding of the sustainability concerns in the cashmere industry, it is important to understand the cashmere supply chain operations to uncover the key sustainability issues prevalent in the present-day traditional cashmere industry. For this, a single case study was conducted in Kashmir, India using qualitative approaches. Data collection was carried out using semi-structured interviews, observations, cashmere retailer websites and documentary evidence. Due to the impact of mechanization and lack of industry standards, the research findings indicate deteriorating socio-economic conditions of the artisans; especially, women spinners and weavers. Mechanization promotes economic sustainability for the manufacturers and retailers which helps them strengthen their market base. However, with this, artisan communities are rendered jobless who are dependent on their manual skills for sustenance as they have limited alternate revenue generation options. Moreover, the lack of motivation among the artisans to use institutional support further escalates sustainability concerns in the traditional craft industry.
Keywords: cashmere industry; sustainability; supply chains; Kashmir pashmina; 12 Built Environment and Design